Dietary intake of vitamin D in the Moroccan adolescents - El-houcine Sebbar; Hicham Sam; Ennouamane Saalaoui; Mohammed Choukri (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2018)
Aims: Most epidemiological studies show that vitamin D defi ciency is frequent in the general population including adolescents. The aim of our work is to evaluate the dietary intake of vitamin D in the Moroccan adolescents. Methods: This study included 257 Moroccan adolescents who performed a vitamin D questionnaire (VDQ), covering the consumption of four foods with high vitamin D content (fi sh, milk, margarine and yoghurt). Results: The average dietary vitamin D intake was 4.6μg/day. This observational study on Moroccan adolescents indicates a high prevalence of insuffi cient vitamin D intake, and below the recommended consumption values, particularly in girls. Conclusion: Inadequate vitamin D intake is common among the adolescents. To fi ght against this situation, initiatives must be implemented, including improved population education, lifestyle and vitamin D supplementation, in order to avoid serious adverse health consequences of bone.